2020
DOI: 10.3389/fonc.2020.01481
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Acquired EGFR T790M-Dependent Resistance to EGFR-TKI Treatment in Lung Adenocarcinoma Patients in Taiwan

Abstract: tissue samples or complications. In conclusion, this study showed that patients who progressed from gefitinib treatment, bearing common EGFR mutations, and with longer EGFR-TKI treatment duration had increased incidence of T790M acquisition and, therefore, were suitable for subsequent osimertinib treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 40 publications
5
29
0
Order By: Relevance
“…Wu et al also indicated that the T790M acquisition rate was no difference between patients who received and patients who did not receive chemotherapy before re-biopsy. 30 Furthermore, in the present study, patients with an uncommon EGFR mutation tended to be less likely to develop a T790M mutation (37.0% for exon 19 deletion, 41.3% for L858R, and 0 for uncommon mutation); this finding was consistent with the results of another recent study. 14,31 The cobas test (v2) of circulating cfDNA has been found to detect 61% of tumor specimens with the T790M mutation.…”
supporting
confidence: 93%
“…Wu et al also indicated that the T790M acquisition rate was no difference between patients who received and patients who did not receive chemotherapy before re-biopsy. 30 Furthermore, in the present study, patients with an uncommon EGFR mutation tended to be less likely to develop a T790M mutation (37.0% for exon 19 deletion, 41.3% for L858R, and 0 for uncommon mutation); this finding was consistent with the results of another recent study. 14,31 The cobas test (v2) of circulating cfDNA has been found to detect 61% of tumor specimens with the T790M mutation.…”
supporting
confidence: 93%
“…Irrespective of the administration of first‐ or second‐generation EGFR‐TKIs in the first‐line setting, acquired T790M mutation accounts for the majority of resistance mechanisms upon disease progression. Several studies, which mainly conducted in the context of gefitinib or erlotinib resistance, have reported a higher secondary T790M in common mutation than in uncommon one, and the T790M rate in EGFR exon 19 deletion tended to be higher than that in EGFR L858R 25‐27 . However, data of secondary T790M from a pure afatinib‐treated cohort in relation to different EGFR mutation subtypes are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Following approval, the Ministry of Health and Welfare in South Korea granted reimbursement for osimertinib in the 2L setting in December 2017 [23]. In Taiwan, reimbursement for osimertinib in the 2L setting was granted in April 2020 [25]. Testing of tumors for T790M in patients with resistance to 1G/2G EGFR-TKIs in the 1L setting is now mandatory, with osimertinib considered the standard of care for patients with T790M-positive tumors [26].…”
Section: Introductionmentioning
confidence: 99%